Origen and Jerome as Exegetes of the Parables from the Gospel of St. Matthew - Elements in Common and Differences - Szram, Mariusz (Vox Patrum, 2024)
The article is an attempt to examine the degree of dependency of Jerome’s exegesis of the parables from the Gospel of St. Matthew on the exegesis of the same texts by Origen. The primary sources are Jerome’s Commentary on the Gospel of St. Matthew written in 398 AD, when he was already an enemy of the Alexandrian, and Origen’s Commentary on the same Gospel. A detailed comparative analysis of the exegesis of the selected parables led to the following conclusions. The differences between the approaches of both authors are limited to three issues: (1) Jerome’s interpretations reflect the spirit of the post-Nicene period, marked by Trinitarian disputes; (2) The Stridonian dissociates himself from all associations with Origen’s dubious theological suggestions, such as the pre-existence of souls or apocatastasis, which can be noticed concealed in the exegesis of the Alexandrian; (3) Jerome’s comments are short and concisely convey the main spiritual meaning of the parables in question, but this difference in the length of comments is quite secondary. Despite the above differences the reliance of the Stridonian on the Alexandrian is significant. Jerome’s elaborations are very similar to those of Origen in terms of exegetic methodology and spiritual content extracted from the text of the Gospel. Even if Jerome does not accept all the solutions proposed by the Alexandrian, he is in constant dialogue with him and remains in his work an Origenist dependent on the allegorical orientation of exegesis.